Curriculum Guidelines for Mathematics degree and Gender and Sexuality issues in Brazil - Flavio Augusto Leite Taveira; Deise Aparecida Peralta (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The objective of this article was to analyze the speech acts present in a curricular document currently in force as a guideline for (re)formulations of undergraduate programs in Mathematics in Brazil. The theoretical and methodological framework adopted is based on the Habermasian perspective of Discursive Ethics. In structural terms, we present discussions on the importance of Gender and Sexuality issues amid the contemporary debate on Mathematics Education. In terms of results, we affirm that the rationality by which the guidelines for undergraduate programs in Mathematics are oriented is characterized as instrumental when considering experiences, reflections, and formative practices that permeate the issues of Gender and Sexuality.